Analisis Semiotika Komunikasi Visual Pada Kemasan Produk Baru Granola Beorganik - Siti Nur Amaliah; Herry Prilosadoso (Institut Seni Indonesia Surakarta, 2024)
Abstract Currently, packaging serves as a crucial communication tool, not only functioning as a protector of the product contents but also playing a role in conveying messages and building brand identity to consumers. This study aims to analyze the meanings contained in the packaging design of Beorganik's Granola product with the